Odpowiedzi

2010-01-15T18:28:47+01:00
A) 2x + 3y + (x - 5y) = 3x - 2y
2x + 3y + x - 5y = 3x - 2y
2x + x - 3x = - 2y + 5y - 3y
0 = 0 - jest tożsamościowe
b) 12x - (2x + 1) - 9(2 - x) = 19x
12x - 2x - 1 - 18 + 9x = 19x
12x - 2x + 9x - 19x = 18 + 1
0 nie = 19 - więc rów. nie jest tożsamościowe
c) 3(x + 21) + (2x - 3) = 5x
3x + 63 + 2x - 3 = 5x
3x + 2x - 5x = 3 - 63
0 nie = -60 - więc rów. nie jest tożsamościowe
d) 2x + 3(x + 2) = 6(x + 1) - x
2x + 3x + 6 = 6x + 6 - x
2x + 3x - 6x - x = 6 - 6
-x nie = 0 - więc rów. nie jest tożsamościowe